Age Estimation for Dental Patients Using Orthopantomographs - Karaarslan, Bekir; Karaarslan, Emine Sirin; Ozsevik, Abdul Semih; Ertas, Ertan (European Journal of Dentistry, 2010)
Objectives: The aim of this study was to conduct age estimates for dental patients using orthopantomographs (OPGs). The OPGs were selected by an independent author with respect to criteria and evaluated by two independent dentists. The results were compared to chronologic ages. The reliability of the estimates, concurrently made by the two independent dentists using OPGs, was also evaluated.Methods: In this retrospective study, the OPGs of 238 Turkish individuals of known chronological age, ranging from 1 to 60 years, were measured. Patients were then classified. Radiographs were evaluated by two independent dentists and age estimation was achieved according to the decades.Results: The truest age estimates made by the dentists were in the 1-10 years age range (89.6%), the most inaccurate age estimates were in the 41-50 years age range (41.7%). Results indicate that the accuracy of age estimation diminishes with age.Conclusions: Despite the variations related to the practitioners, in this study, there were no significant differences in age estimations between the two participant practitioners. Age estimation through evaluating OPGs was the most accurate in the first decade and the least in fourth decade. It can be concluded that OPGs are not adequate for accurate age estimation. (Eur J Dent 2010;4:389-394)
Keywords: Age estimation; Forensic dentistry; Orthopantomographs